PLK1 Inhibitor as a Novel Therapy for Triple-Negative Breast Cancer - Djuanda, Louis Felix; Kurniawan, Jennifer Nathalie; Purnamsidi, Wilbert (Essential: Essence of Scientific Medical Journal; Vol 21 No 2 (2024): Volume 21 No. 2 (Juli - Desember 2023) Essential: Essence of Scientific Medical Journal, 2024)
Introduction: The prevalence of Breast Cancer has increased throughout the years. The disease also carries a high risk of mortality. The receptors found on breast cancer cells are essential considerations in determining effective therapy and prognosis. Triple Negative Breast Cancer (TNBC) is a subtype of breast cancer that does not express most of the receptors that usually expressed by breast cancer cells. This subtype has high mortality, one of which is due to limited therapeutic options and low efficacy, therefore increasing the need of new therapy for TNBC. Discussion: Overexpression of polo-like kinase 1 (PLK1) is associated with poor prognosis in TNBC. Excessive PLK1 activity causes high cell proliferation and increases cell proliferation stress so that cell chromosome instability can occur. PLK1 inhibitors work by affecting the cell cycle and apoptosis of cancer cells. Currently, the metabolic mechanism of PLK1 inhibitors is not clearly known, but it has been proven that absorption through oral administration is quite good. Side effects from using PLK1 inhibitors are common, but most can be managed Conclusion: Considering the limited treatment options for TNBC and the relatively good efficacy of PLK1 inhibitors, this encourages the recommendation to use PLK1 as a TNBC therapy, especially in patients with therapy resistance, regardless of the side effects that can be caused.